Analisis Yuridis Perlu Tidaknya Peraturan Desa tentang Penyertaan Modal BUM Desa: Studi Kasus di Kabupaten Kudus - Khomsin, Moh Ali (Penerbit Goodwood, 2023)
Purpose: find legal arguments whether or not a (special) village regulation on capital participation to BUM Desa is necessary? Methodology: Using a normative juridical approach, to find legal arguments about whether or not a (special) village regulation on capital participation is necessary according to Peraturan Bupati Kudus Nomor 30 Tahun 2018 concerning Village Financial Management with Peraturan Pemerintah Number 11 of 2021 concerning Badan Usaha Milik Desa Results: Based on the legal principle of lex superiori derogat legi inferiori, several articles in Peraturan Bupati Kudus 30/2018 (including Permendagri 20/2018), especially those concerning the establishment and capital participation of BUM Desa, are declared invalid. Because there is already a higher regulation, namely PP Number 11 of 2021 concerning BUM Desa. It is explicitly stated in Article 77 of PP 11/2021, that all implementing regulations governing BUM Desa / joint BUM Desa are declared to still apply, as long as they do not conflict with the provisions in PP 11/2021. Thus, there is no need for a special village regulation on BUM Desa capital participation. Because the BUM Desa regulation with PP 11/2021 is very clear, the establishment of BUM Desa is stipulated by perdes, which in the perdes contains a determination of the amount of village capital participation. And if there is an increase in capital, an amendment to the peraturan desa regarding the BUM Desa articles of association (peraturan desa establishment) is made. Limitations: This research only focuses on the regulation of BUM Desa both regarding capital and the process of establishing BUM Desa after PP 11/2021 in Kudus Regency. Contribution: Provide legal arguments for the lack of need for peraturan desa on BUM Desa capital participation in Kabupaten Kudus.